Lightweight key agreement protocol for IoT based on IKEv2. (November 2017) - Lavanya, M.; Natarajan, V.
Abstract: The future of wireless sensor networks is in providing IP connectivity to all the nodes in the network. 6LoWPAN is an adaptation layer which allows the IEEE 802.15.4 network to communicate using IPv6 addresses. Security in 6LoWPAN is an important issue to be taken into consideration. The nodes are limited in terms of energy, memory and processing power. Therefore, including security will be an additional cost, but nevertheless it is mandatory in certain applications like e-health monitoring, building-structure monitoring, etc. Therefore, as a part of providing end-to-end security in wireless sensor networks, a novel lightweight key agreement and authentication protocol has been proposed. This protocol is implemented in NS-2 and a performance comparison is made with the existing IKEv2 protocol.